Hedge strategies with future contracts for the commodities trading in feedlot beef cattle - Badaró, Gustavo De Souza Campos; Fontes, Renato Elias; Gonçalves, Tarcísio De Moraes [UNESP]; Júnior, Luiz Gonzaga De Castro; De Souza, Waldemar Antonio Da Rocha (My University, 2017)
The study applies the futures markets trade, for the market demands of the production activity of the feedlot beef cattle. Presenting the aim of identifying placement strategies in futures contracts, that articulate a better relationship between risk and returns for the purchase of inputs and sale of cattle in the production of feedlot beef cattle. Were analyzed positioning in future contracts, established on account of payments typical to this production system, applied to a hypothetical model. We performed an historical analysis of the hedge operations, by means of simulating costs and revenues, with contracts for input purchases: unfinished cattle (BGI), corn (CCM) and soybeans (SOJ), and for production sale, contracts of live cattle (BGI). With the individual evaluation of positionings tested on future markets, have been identified two strategies that constitute the best relationship between risk and returns.Yielding, respectively, 3.97% and 3.58% more than the average obtained with the spot market, and a lower variability of profit margins over the years. It was concluded that the strategic positions defined in futures contracts allow higher gains than on the spot market, in risk reduced conditions.
Keywords: Feedlot cattle; Future markets; Hedge